204 The Canadian Injury Prevention Curriculum: using an integrated knowledge-translation approach. (1st September 2016) - Richmond, Sarah A; Belton, Kathy; Heatley, Jennifer; Black, Amanda; Fridman, Liraz; Ezzat, Allison; Clemens, Tessa; Pike, Ian; Macpherson, Alison
Abstract : Background: Intentional and unintentional injuries are a significant and preventable health concern in Canada with 4.27 million Canadians ages 12 or older suffering an activity limiting injury. Knowledge translation and education among researchers, practitioners and policy makers as well as the continual development of trainees in the area of injury prevention, is paramount for the future health of Canadians. Methods: The Canadian Injury Prevention Curriculum (CIPC) was designed to provide practitioners the understanding of the theory and practice of injury prevention along with the tools needed to develop and implement effective injury prevention programs. The CIPC is targeted toward adult learners (researchers, practitioners and/or policy makers) who develop, implement and/or evaluate programs aimed at reducing the frequency and severity of both intentional and unintentional injury. The last update of this curriculum was in 2010. This project aimed to update the CIPC, using an integrated knowledge translation approach to reflect an evidence-informed approach to injury prevention. Results: The revision occurred over a series of phases: PHASE 1 – Update to the current curriculum to reflect an evidence-informed approach to injury prevention (what is injury prevention and defining the problem, risk and protective factors and key determinants of injury, designing/selecting an intervention, implementation and evaluation) in consultation with an adult learning expert; PHASE 2 – Modules were developed for practitioners to further knowledge and application of core knowledge; PHASE 3 – The updated curriculum was made available across Canada to researchers, practitioners and policy makers interested in preventing injury in Canada. Conclusions: The CIPC was updated using an integrated knowledge translation approach. The result was an education tool using an evidence-informed approach to the prevention of injury, applicable for researchers, practitioners, policy makers, and junior trainees.